PEMBERIAN PERINTAH KERJA DALAM MASA CUTI BAGI PEKERJA, WAJIBKAH? - Sitohang, Mawar (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
One of the fundamental rights of workers/laborers at work is the right to leave which is granted by law, and its implementation needs to be guaranteed in the employment relationship between workers/laborers and employers. Workers taking leave means that workers are given the opportunity to take time off from work. However, it is not uncommon for employers to still ask workers to do work while on leave. This is a problem for workers, whether they should do their work or not? If work orders from superiors are not carried out, the consequences can be detrimental to workers. So how are workers' leave rights regulated according to labor law, and what steps must workers take if they receive a work order while on leave? This research will examine this problem using normative research that examines secondary data using a statutory approach. Based on the results of the research, it was found that work orders to employees while on leave constitute a violation of the work agreement and are detrimental to the worker so that it is an act of breaking the employer's promise to the worker.